Modelling and simulation of extrusion force in biomass pelletisation by ring die pellet mill. (15th October 2020) - Liu, Jie; Na, Risu; Cen, Haitang
The periodic change in extrusion force is the main cause of vibration in a ring die pellet mill. The generated vibration shortens the life of the ring die and also decreases its reliability and stability. According to the principle of biomass pelletisation, a new model of cyclic extrusion force calculation was established, in this paper, by considering the changes in distance between ring die and roller against time. A dynamic simulation model of a ring die pellet mill with eccentricity was developed in LS-DYNA software, and the internal stress distribution of biomass was calculated. The obtained results revealed that the internal stress on biomass and the angle of extrusion both gradually decreased with the increasing distance between ring die and roller. The relationship between distance and extrusion force was linear when the distance was in the range of 0.5-1.5 mm. Extrusion force manifested a periodic variation, and its frequency was consistent with the rotational frequency of the ring die. The vibration amplitude of extrusion force was related to the eccentricity of the ring die.